Exceptional Photocatalytic Activities of rGO Modified (B,N) Co‐Doped WO3, Coupled with CdSe QDs for One Photon Z‐Scheme System: A Joint Experimental and DFT Study - Raziq, Fazal; Aligayev, Amil; Shen, Huahai; Ali, Sharafat; Shah, Rahim; Ali, Sajjad; Bakhtiar, Syedul H.; Ali, Asad; Zarshad, Naghat; Zada, Amir; Xia, Xiang; Zu, Xiaotao; et al. (Advanced science, 2022)
Artificial Z‐scheme, a tandem structure with two‐step excitation process, has gained significant attention in energy production and environmental remediation. By effectively connecting and matching the band‐gaps of two different photosystems, it is significant to utilize more photons for excellent photoactivity. Herein, a novel one‐photon (same energy‐two‐photon) Z‐scheme system is constructed between rGO modified boron‐nitrogen co‐doped‐WO3, and coupled CdSe quantum dots‐(QDs). The coctalyst‐0.5%RhxCr2O3(0.5RCr) modified amount‐optimized sample 6%CdSe/1%rGO3%BN‐WO3 revealed an unprecedented visible‐light driven overall‐water‐splitting to produce ≈51 µmol h−1 g−1 H2 and 25.5 µmol h−1 g−1 O2, and it remained unchanged for 5 runs in 30 h. This superior performance is ascribed to the one‐photon Z‐scheme, which simultaneously stimulates a two photocatalysts system, and enhanced charge separation as revealed by various spectroscopy techniques. The density‐functional theory is further utilized to understand the origin of this performance enhancement. This work provides a feasible strategy for constructing an efficient one‐photon Z‐scheme for practical applications. The design of a novel Z‐scheme system based on a band gap adjusted visible‐light responsive 0.5RCr/6CdSe/1rGO/3BN‐WO3 nanocomposite is successfully constructed via hydrothermal method. This work demonstrates a promising approach to synthesize nanophotocatalysts based on WO3 for visible‐light driven solar energy application.